2021
DOI: 10.1007/s00170-020-06532-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shot peening and artificial surface defects on fatigue properties of 50CrV4 steel

Abstract: Shot peening processes are commonly used for improving the fatigue properties of steels. Shot peening introduces a compressive residual stress field in the near surface of steel, which can reduce or stop the growth of fatigue cracks and improve fatigue properties. This study experimentally investigated the effect of shot peening on the fatigue properties of 50CrV4 steel alloys with different artificial surface defects. Drilling tools were used to introduce different artificial defects with root radii of 0.585 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
(51 reference statements)
0
4
0
3
Order By: Relevance
“…An as‐received notch surface (with corrosion pitting) typically had a lower number of crack initiation events, possibly due to the onset of early initiation activity and growth behavior inhibiting later crack initiation due to shielding effects 1 . The shot peened notch surface typically had more crack initiation events than a polished or as‐received notch surface, especially at lower strain ranges due to the presence of pre‐existing cracks before testing (Figure 14), a feature seen in similar shot peened steels 6,23,24 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…An as‐received notch surface (with corrosion pitting) typically had a lower number of crack initiation events, possibly due to the onset of early initiation activity and growth behavior inhibiting later crack initiation due to shielding effects 1 . The shot peened notch surface typically had more crack initiation events than a polished or as‐received notch surface, especially at lower strain ranges due to the presence of pre‐existing cracks before testing (Figure 14), a feature seen in similar shot peened steels 6,23,24 …”
Section: Discussionmentioning
confidence: 94%
“…1 The shot peened notch surface typically had more crack initiation events than a polished or as-received notch surface, especially at lower strain ranges due to the presence of pre-existing cracks before testing (Figure 14), a feature seen in similar shot peened steels. 6,23,24 The number of crack initiation events observed on a shot peened U-notch surface made from FV448 with applied strain ranges between 0.6% and 0.9% 10 were almost doubled when assessed in the FV566 at the same strain range. This difference can be attributed to the method used to count the number of initiation events on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with the findings expressed by other Refs. [48][49][50][51]. As depicted in Fig.…”
Section: Phase Analysismentioning
confidence: 99%
“…For instance, it has been demonstrated that ultrasonic impact peening (UIP) technology plays a positive role in refining the grain size and increasing hardness and wear resistance. [8,9] In addition, the residual compressive stress was applied to the metal surface, which can heal the microcracks and holes during the cycle wear. [10] Yin et al [11,12] found that the ultrasonic shot peening (USP) can induce nanocrystalline structure on the surface, thereby improving the nanohardness and Young's modulus.…”
Section: Introductionmentioning
confidence: 99%